Analisis Project Based Learning (PjBL) Untuk Kemampuan Berpikir Kreatif Anak Usia 5-6 Tahun - Xena Palapessy; Mallevi Agustin Ningrum; Kartika Rinakit Adhe; Melia Dwi Widayanti (UNIB Press, 2023)
Learning in early childhood should be packaged into fun and meaningful activities, with child-centered learning and developing children's creative thinking. Children's creative thinking has 4 indicators, originality, fluency, elaborative, flexibility. The existence of project-based learning (PjBL) allows children to develop their creative thinking through project learning that has been prepared by the teacher according to children's interests, children's needs and children's age. By confronting children with a problem, children's knowledge will develop and children can solve problems, develop ideas or ideas according to their own thoughts and children are able to create a product from their own ideas. The purpose of this study was to determine the planning, implementation and evaluation of project-based learning (PjBL) for the creative thinking skills of children aged 5-6 years. This research method uses descriptive qualitative with a case study approach, the data obtained is the result of interviews, observation and documentation. The uniqueness of the findings of this study is that project-based learning (PjBL) in TK Negeri Pembina Surabaya is carried out every day for a week, based on the results of research that has been conducted on project-based learning (PjBL) for children's creative thinking, showing that of the 4 indicators of creative thinking only 3 indicators are dominant, namely flexibility, originality and elaboration while 1 weak indicator is fluency.